Chapter Interpretations. Market, Work, Training - Malavasi, Pierluigi (Studies on Adult Learning and Education, 2018)
What of the job market in the era of Brexit and in the international arena of the Trump presidency? Naturally, there are various perspectives, but forms of emotive or propagandist rhetoric threaten to hold sway here. Above all, Guidance Towards the Job market means recognizing the complexities of geopolitical change within our information-sharing and collaborative networks, as well as the various and contrasting interpretations that arise. The current decline of the European Union − of which the UK public referendum result is symptomatic − and the 'America First' slogan, now a distinguishing feature of the current US government, are only two of the multiple forces interacting and defining pervasive transformations in economic, labour, and educational policies